Multi-criteria decision analysis for setting priorities on HIV/AIDS interventions in Thailand - Youngkong Sitaporn; Teerawattananon Yot; Tantivess Sripen; Baltussen Rob (BMC, 2012)
Abstract Background A wide range of preventive, treatment, and care programs for HIV/AIDS are currently available and some of them have been implemented in Thailand. Policy makers are now facing challenges on how the scarce resources for HIV/AIDS control can be spent more wisely. Although effectiveness and cost-effectiveness information is useful for guiding policy decisions, empirical evidence indicates the importance of other criteria, such as equity and the characteristics of the target population, also play important roles in priority setting. This study aims to experiment with the use of multi-criteria decision analysis (MCDA) to prioritise interventions in HIV/AIDS control in Thailand. Methods We used MCDA to rank 40 HIV/AIDS interventions on the basis of the priority setting criteria put forward by three groups of stakeholders including policy makers, people living with HIV/AIDs (PLWHA), and village health volunteers (VHVs). MCDA incorporated an explicit component of deliberation to let stakeholders reflect on the rank ordering, and adapt where necessary. Results Upon deliberation, policy makers expressed a preference for programs that target high risk groups such as men who have sex with men, injecting drug users, and female sex workers. The VHVs preferred interventions that target the youth or the general population, and gave lower priority to programs that target high risk groups. PLWHA gave all interventions the same priority. The rank order correlation between the priorities as expressed before and after deliberation was 37% among the policy makers and 46% among the VHVs. Conclusion This study documented the feasibility of MCDA to prioritize HIV/AIDS interventions in Thailand, and has shown the usefulness of a deliberative process as an integrated component of MCDA. MCDA holds potential to contribute to a more transparent and accountable priority setting process, and further application of this approach in the prioritisation of health interventions is warranted.